(untitled) (European Journal of Pedagogical Initiatives and Educational Practices, 2025)
This article discusses the process of a person entering into communication with different people in the process of his activity and the formation of his qualities of perfection on this basis. The tasks of people as a process of interpersonal exchange of information, knowledge, ideas, opinions through this communication are considered. The mutual joint action of those entering into a relationship is a speech process, in which it is carried out not only with words, but also with gestures, gestures, and their ability to perceive each other.